A new cardiovascular disease risk factor for young adults: Preterm birth. Issue 12 (28th December 2022) - Brewer, Pamela L.; D'Agata, Amy L.; Sullivan, Mary C.
ABSTRACT: Adults born preterm (birth <37 weeks' gestation) have a two-fold increased risk of early cardiovascular mortality. With 10% of the U.S. population born prematurely and perinatal advancements dramatically improving survival rates, millions of survivors are now reaching adulthood. This phenomenon has introduced a whole new population of individuals with a history of preterm birth. Although the prevailing notion has been that preterm birth is a condition confined only to infancy and early childhood, we now know preterm birth is a risk for lifelong chronic health conditions. Despite almost a decade of epidemiological evidence showing increased cardiovascular risk for those born preterm, this has not yet been translated into clinical practice. As a result, clinicians are caring for adults born prematurely without screening and treatment guidelines for this at-risk population and few inquire about birth history during clinical encounters. This brief report presents growing evidence about disrupted cardiogenesis and consequential structural and functional modifications. By asking the question "Were you born preterm?, " nurse practitioners can take the first step of increasing their awareness of this at-risk population and mitigate adverse cardiovascular outcomes by using preterm birth as a risk factor when determining health promotion and treatment decisions.